Allowance or service: Public attitudes toward childcare‐related family policies in China - Fan, Xin; Ngok, Kinglun (Social policy & administration, 2025)
Childcare has been considered a ‘new’ social risk and various childcare regimes have been developed worldwide to tackle this social problem. While welfare attitude studies have paid attention to public attitudes toward childcare services, little is known about public attitudes toward other childcare‐related family policies (i.e., leave and allowance). Using novel and unique survey data on welfare attitudes from China, this article investigates how socioeconomic factors matter to general as well as prioritised support for three types of childcare‐related family policies and to policy regimes in China where low fertility crisis is emerging. The survey data suggests the biggest gap between general and prioritised support is found in allowance policy and the smallest in service policy. Regression models suggest that the biggest gap between general and prioritised support for allowance policy can be explained by the reversed and negative effects of education and gender. We further develop a typology of public support for childcare regimes using Latent Class Analysis (LCA) and find four types: implicit and explicit familialism, de‐familialism, and ambiguous familialism. The results of multinomial logistic regression on public support for childcare regimes confirm the findings on prioritised support for different policies and suggest a bifurcation effect of age on regime preferences. We discuss the implications of the findings in the conclusion.